ASSESSMENT OF MAXILLOFACIAL TRAUMA IN KANJURUHAN GENERAL HOSPITAL MALANG USING FACIAL INJURY SEVERITY SCALE (FISS) SCORING SYSTEM - Kunthi Kencana Makayasa Putri; Deddy Setyo Nugroho (Jurnal Rekonstruksi dan Estetik)
Highlights: